Comparative analysis of root transcriptome profiles of two pairs of drought-tolerant and susceptible rice near-isogenic lines under different drought stress - Moumeni, A.; Satoh, K.; Kondoh, H.; Asano, T.; Hosaka, A.; Venuprasad, R.; Serraj, R.; Kumar, A.; Leung, H.; Kikuchi, S. (Springer, 2011)
Background: Plant roots are important organs to uptake soil water and nutrients, perceiving and transducing of soil water deficit signals to shoot. The current knowledge of drought stress transcriptomes in rice are mostly relying on comparative studies of diverse genetic background under drought. A more reliable approach is to use near-isogenic lines (NILs) with a common genetic background but contrasting levels of resistance to drought stress under initial exposure to water deficit. Here, we examined two pairs of NILs in IR64 background with contrasting drought tolerance. We obtained gene expression profile in roots of rice NILs under different levels of drought stress help to identify genes and mechanisms involved in drought stress. Results: Global gene expression analysis showed that about 55% of genes differentially expressed in roots of rice in response to drought stress treatments. The number of differentially expressed genes (DEGs) increased in NILs as the level of water deficits, increased from mild to severe condition, suggesting that more genes were affected by increasing drought stress. Gene onthology (GO) test and biological pathway analysis indicated that activated genes in the drought tolerant NILs IR77298-14-1-2-B-10 and IR77298-5-6-B-18 were mostly involved in secondary metabolism, amino acid metabolism, response to stimulus, defence response, transcription and signal transduction, and down-regulated genes were involved in photosynthesis and cell wall growth. We also observed gibberellic acid (GA) and auxin crosstalk modulating lateral root formation in the tolerant NILs. Conclusions: Transcriptome analysis on two pairs of NILs with a common genetic background (~97%) showed distinctive differences in gene expression profiles and could be effective to unravel genes involved in drought tolerance. In comparison with the moderately tolerant NIL IR77298-5-6-B-18 and other susceptible NILs, the tolerant NIL IR77298-14-1-2-B-10 showed a greater number of DEGs for cell growth, hormone biosynthesis, cellular transports, amino acid metabolism, signalling, transcription factors and carbohydrate metabolism in response to drought stress treatments. Thus, different mechanisms are achieving tolerance in the two tolerant lines.